2013
DOI: 10.1016/j.bbi.2013.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Heroin-induced conditioned immunomodulation requires expression of IL-1β in the dorsal hippocampus

Abstract: Opioid-associated environmental stimuli elicit robust immune-altering effects via stimulation of a neural circuitry that includes the basolateral amygdala and nucleus accumbens. These brain regions are known to have both direct and indirect connections with the hippocampus. Thus, the present study evaluated whether the dorsal hippocampus (DH), and more specifically interleukin-1 beta (IL-1β) within the DH, is necessary for the expression of heroin-induced conditioned immunomodulation. Rats received five Pavlov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 77 publications
1
25
0
Order By: Relevance
“…Physiological evidence that cytokines influence synaptic plasticity is also supported by behavioral evidence that central cytokine signaling influences learning in several paradigms, including fear conditioning (Yirmiya and Goshen 2011;Szczytkowski, Lebonville et al 2013). For example, acute administration of either TNF-α or IL-1β and chronic administration of interleukin-6 (IL-6) enhanced memory performance in a passive avoidance paradigm (Matsuda, Wen et al 1996;Yirmiya, Winocur et al 2002;Brennan, Beck et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Physiological evidence that cytokines influence synaptic plasticity is also supported by behavioral evidence that central cytokine signaling influences learning in several paradigms, including fear conditioning (Yirmiya and Goshen 2011;Szczytkowski, Lebonville et al 2013). For example, acute administration of either TNF-α or IL-1β and chronic administration of interleukin-6 (IL-6) enhanced memory performance in a passive avoidance paradigm (Matsuda, Wen et al 1996;Yirmiya, Winocur et al 2002;Brennan, Beck et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…This receptor also binds to IL-1 alpha (IL-1α) and mediates its action, so the specificity of IL-1β in mediating the effects seen cannot be concluded definitively. Previous studies have shown that IL-1β signaling is required for the expression of heroin conditioned immunosuppression to a context through knockdown of IL-1β expression using IL-1β siRNA (Szczytkowski et al, 2013). For the current experiment, IL-1β siRNA was not temporally specific enough to target processes only during or shortly after each conditioning session.…”
Section: Discussionmentioning
confidence: 99%
“…Rats received five, 60-min conditioning sessions every other day as in prior studies, which has been shown to be sufficient to generate conditioned immunosuppression to the heroin-paired context (Szczytkowski et al, 2011; Szczytkowski et al, 2013; Szczytkowski and Lysle, 2010). Each conditioning session involved heroin administration (US) immediately followed by placement into a conditioning chamber (BRS/LVE, Laurel, MD, USA; W 30.5 cm × D 24.1 cm × H 26.7 cm) that served as the conditioned stimulus (CS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations